Effect of Pre Slaughter Fasting On Physical Quality of Broiler Meat - Indra, Rusmin; Apada, Andi Magfira Satya; Rasdiyanah, Rasdiyanah (Universitas Halu Oleo, 2022)
Assessment of meat physical quality is the way to choosing meat. Pre slaughter time is one method to restorate livestock (including poultry) prior to deductions so that animals do not wage for too long at the time of slaughter. This study aims to determine the effect of pre slaughter fasting on the quality of meat produced. This study using 24 samples of broiler chickens. The sample is divided into 4 groups where group 1 without treatment; group 2 4 hours of fasting; group 3 8 hours of fasting; and group 4 12 hours of fasting. The parameters include specific gravity, pH, color, tenderness, and water holding capacity. The result of this study found that fasting on broiler chickens up to 12 hours did not give a significant effect on specific gravity, tenderness, and water holding capacity. Pre slaughter fasting until 12 hours only gives effect to pH and color of meat. The fasting time is 8 - 12 hours before slaughter not recommended because it has the biggest pH possible to get pale, soft, exudative (PSE) .